2001
DOI: 10.1097/00002030-200109280-00026
|View full text |Cite
|
Sign up to set email alerts
|

Variation in breastmilk HIV-1 viral load in left and right breasts during the first 3 months of lactation

Abstract: The mechanism and risk factors associated with mother-to-child transmission of HIV-1 through breastfeeding remain unclear; breastmilk viral load may be an important determinant of transmission. Analysis of breastmilk cell-free viral load in samples taken from each breast at 1, 6 and 14 weeks postpartum showed that HIV-1 is shed intermittently and load may differ considerably between breasts of an individual woman at any given time. Breastmilk HIV-1 load was undetectable in approximately one-third of samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2003
2003
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 6 publications
1
24
0
2
Order By: Relevance
“…This is consistent with our previously published work as well as that of others (11,12). Higher levels of Ag could not explain the higher frequency of Ag-specific cells, since in the case of HIV infection, breast milk contains much less HIV than plasma (12,17,29). In addition, compared with their counterparts in blood, breast milk CD8 ϩ T cells lack expression of CCR7, CD62L, and CD45RA and express high levels of CD45RO.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with our previously published work as well as that of others (11,12). Higher levels of Ag could not explain the higher frequency of Ag-specific cells, since in the case of HIV infection, breast milk contains much less HIV than plasma (12,17,29). In addition, compared with their counterparts in blood, breast milk CD8 ϩ T cells lack expression of CCR7, CD62L, and CD45RA and express high levels of CD45RO.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously demonstrated that this assay can reproducibly and reliably detect HIV in breast milk (14). In addition, we and others (15)(16)(17) have shown that breast milk RNA levels are at least 10-to 100-fold less than those found in the blood. The breast milk RNA levels in the HIV-infected women in this study were all Ͻ50 copies/ml.…”
Section: Quantitation Of Hiv-1 Rna In Plasma and Breast Milkmentioning
confidence: 67%
“…Rapid transition from exclusive breast milk to full replacement feedings might further decrease the risk of transmission by minimizing the concurrent exposure to nonbreast milk substances and HIV-containing breast milk. It is speculated that pathogen-or allergen-containing foods taken with mixed feeding may increase gut permeability or mucosal inflammation [5], and/or incomplete breast emptying may lead to subclinical mastitis [6] and increased breast milk viral load [7]. Although it is difficult to conceive of other settings where the discomfort and potential harm produced by rapid weaning might have a net benefit, abrupt and complete cessation of exclusive breastfeeding may have an important role in reducing postnatal transmission of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been observed that the cell-free viral load in breast milk at 1, 6 and 14 weeks postpartum varies considerably between the right and left breast of an individual woman at any given time. Breast milk HIV-1 load was undetectable in approximately one third of the samples [7] .…”
Section: Maternal Viral Load and Cd4 Countmentioning
confidence: 98%